När hände 1968? - Alf Arvidsson (Kulturella Perspektiv)
The present article begins with a discussion of how "the Sixties" and "1968" became significant ideological concepts in public debate, used in order to contrast ideas concerning the societies of today and tomorrow. Furthermore, this article advocates that the 1960s be considered an object of critical ethnological research, which identifies and emphasizes the long-term changes in cultural patterns which constitute the dynamics of the 1950s, 60s and 70s. Two fundamental questions of a methodological nature are therewith actualized. The first concerns the mass media's place within ethnological research. As ethnologists, we must see the mass media as something which does not simply reflect and/or influence everyday life, but which also constitutes a central component of everyday life. Another question concerns the fact that a study of the 1960s unconditionally implies a study of politics, and thus questions must be posed as to how power is constituted and how "politics" as a concept is constructed.